cHPP controller: A High Performance Hyper-node Hardware Accelerator - Yong Su; Feilong Liu; Zheng Cao; Zhan Wang; Xiaoli Liu; Xuejun An; Ninghui Sun (Proceedings (International Symposium on Parallel and Distributed Computing), 2013)
The high-density blade server provides an attractive solution for the rapid increasing demand on computing. The degree of parallelism inside a blade enclosure nowadays has reach up to hundreds of cores. In such parallelism, it is necessary to accelerate communications inside a blade enclosure. However, commercial products seldom set foot in the optimization based on hardware. A hyper-node controller is proposed to provide a low overhead and high performance interconnection based on PCIe, which supports global address space, user-level communication, and efficient communication primitives. Furthermore, the efficient sharing of I/O resource is another goal of this design. The prototype of the hyper-node controller is implemented in FPGA. The testing results show the lowest latency is only 1.242us and the highest bandwidth is 3.19GB/s, which is almost 99.7% of the theoretic peak bandwidth.